South African Sawmill Industry Clusters and Benchmarking Practices - Tshavhungwe, V.; Grobbelaar, S. (South African Journal of Industrial Engineering, 2025)
Sawmills tend to be concentrated where there is an adequate supply of logs for processing. The concentration of these sawmills presents an excellent opportunity to form successful industry clusters and for firms to be benchmarked against other firms in the industry. The study evaluated benchmarking practices in the South African sawmill industry. It used an online survey methodology to examine how cooperation between the industry players could enhance the industry’s competitiveness. The results gave valuable insights into the views of individuals working in various sawmills. The study could assist sawmillers to evaluate their processes and to consider implementing various forms of benchmarking in order to improve their sawmills in collaboration with multiple stakeholders.